Bevacizumab Eye Drops Vs. Intra-meibomian Gland Injection of Bevacizumab for Meibomian Gland Dysfunction-Associated Posterior Blepharitis - Tantipat, Chitchanok; Kasetsuwan, Ngamjit; Chotikkakamthorn, Patraramon; Pongpirul, Krit (Frontiers in Medicine, 2022)
Aims: This study aimed to evaluate the efficacy and safety of bevacizumab eye drops compared with those of an intra-meibomian gland (MG) injection of bevacizumab when performed in conjunction with standard lid hygiene in patients with meibomian gland dysfunction (MGD)-associated posterior blepharitis. Methods: This prospective, open-label, observer-blinded randomized controlled trial included 60 eyes of 30 patients with MGD-associated posterior blepharitis who exhibited lid margin telangiectasia, treated at the Chula Refractive Surgery Center of King Chulalongkorn Memorial Hospital. Patients were randomized to receive lid hygiene plus 0.05% bevacizumab eye drops or a single intra-MG injection of 2.5% bevacizumab. All patients were instructed to perform routine lid hygiene care as demonstrated in an instructional video. Primary outcomes included telangiectasia grading and the lid margin neovascularized area (LMNA). Secondary outcomes included the Ocular Surface Disease Index (OSDI) score, corneal staining, meibum quality, meiboscore, conjunctival redness, fluorescein break-up time (FBUT), lipid layer thickness, treatment compliance, and adverse events. All parameters were evaluated before and 3 months after treatment. Results: After treatment, there were no significant differences in telangiectasia grade and LMNA between groups (mean difference, −0.14, 95% CI −0.42 to 0.15, p=0.338, −0.1, 95% CI −1.1 to 0.8, p=0.761, respectively); however, the injection group exhibited significant improvements in both telangiectasia grade and LMNA, while, in the eye drop group, only telangiectasia grade showed a significant improvement relative to baseline. The injection group also exhibited significant improvements in corneal staining (mean difference, −0.78, 95% CI −1.29 to −0.27, p=0.003), meiboscores (mean difference, −0.37, 95% CI −0.52 to −0.21, p<0.001), and FBUT (mean difference, 1.25, 95% CI 0.21 to 2.29, p=0.019) compared to the eye drop group. OSDI scores, corneal staining, meibum quality, meiboscores, and conjunctival redness significantly improved relative to baseline in both groups. No local and systemic adverse event was observed at month 3 in both groups. Conclusion: When performed with regular lid hygiene, intra-MG injection and topical application of bevacizumab are safe and effective for improving lid margin telangiectasia and the signs and symptoms of MGD-associated posterior blepharitis. This therapy may represent an alternative or adjunctive treatment for patients with MGD-associated posterior blepharitis.